The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1590/s1413-81232009000500035
|View full text |Cite
|
Sign up to set email alerts
|

Cidadãos peregrinos: os "usuários" do SUS e os significados de sua demanda a prontos-socorros e hospitais no contexto de um processo de reorientação do modelo assistencial

Abstract: Cidadãos peregrinos: os "usuários" do SUS e os significados de sua demanda a prontos-socorros e hospitais no contexto de um processo de reorientação do modelo assistencial Travelling citizens: the "users" of the Brazilian Unified Health System and the meanings of its demand to the health care emergency services in the context of a process of assistential model reorientation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
33

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 10 publications
0
13
0
33
Order By: Relevance
“…Nessa proposta, o usuário tem acesso aos serviços no tempo e no espaço que lhe são mais adequados, utilizando a tecnologia apropriada a sua necessidade, seja na UBS, no pronto-socorro ou no hospital. A definição inflexível da Atenção Básica como porta de entrada do sistema, com referência territorial, não promove a inclusão e dificulta o acesso dos usuários (12) . A preferência da população pela procura pelo atendimento em serviços de pronto-atendimento também foi constatada em um estudo que avaliou o perfil de usuários de serviços de urgência de média complexidade (13) , bem como de serviços de urgência hospitalares tanto para adultos (14) , como pediátrico (15) .…”
Section: Discussionunclassified
“…Nessa proposta, o usuário tem acesso aos serviços no tempo e no espaço que lhe são mais adequados, utilizando a tecnologia apropriada a sua necessidade, seja na UBS, no pronto-socorro ou no hospital. A definição inflexível da Atenção Básica como porta de entrada do sistema, com referência territorial, não promove a inclusão e dificulta o acesso dos usuários (12) . A preferência da população pela procura pelo atendimento em serviços de pronto-atendimento também foi constatada em um estudo que avaliou o perfil de usuários de serviços de urgência de média complexidade (13) , bem como de serviços de urgência hospitalares tanto para adultos (14) , como pediátrico (15) .…”
Section: Discussionunclassified
“…Difficult access, assumption of inability and lack of confidence in the resolution of the problem, and inexistence of vacancies for obtaining care in primary care services are possible causes that can induce the direct demand for the Emergency Care Units, corroborating with the delay found among patients who sought primary services within this study. Such behavior is not conducive to organization of the demand and the care of chronic conditions such as TB, since Emergency Care units do not have a role in care coordination (7,13,(21)(22) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies identified users' preference for emergency services, instead of health professionals or units to which they have a connection (11)(12)(13) . The phenomenon of spontaneous search for emergency services has been associated with the user's perception of signs and symptoms of health impairment.…”
Section: Discussionmentioning
confidence: 99%